Development of Science Teachers' TPACK: East Asian Practices - Hsu, Ying Shao (Springer, 2016)
Science is a subject matter that requires learners to explore the world and develop their own abilities on the basis of that exploration. As technology broadens and deepens, science teachers need to expand their Technological Pedagogical Content Knowledge (TPACK), which determines how well they use technology to help students learn science. The book details our efforts to prepare science teachers to teach with the help of technology, examining various aspects of teacher education, professional development and teaching material preparation. It consists of three parts, which focus on: how TPACK is conceptually constructed within the field of science education, how teacher evaluation and teaching materials are developed and utilized based on the transformative model and how science teachers are prepared and supported with electronic resources based on the integrative model. The book offers a valuable resource for all those working in science education, as well as those readers who are interested in teacher education. Science teachers will come to know how simulations and animations can pedagogically support student learning. Practices for teachers’ TPACK development such as learning-by-design, evaluation and measurement and teacher communities are also addressed, applied and discussed in the case of science teachers. The individual chapters will provide teacher educators and researchers from all disciplines with new insights into preparing teachers for the Digital Era.